DEVELOPMENT OF E-STORYBOARD APPLICATION MEDIA TO TEACH WRITING SKILLS - Binti Sholikah; Widiarini Widiarini; Siti Rofiah (PROJECT (Professional Journal of English Education), 2023)
Learning media is a tool that functions to convey material or information in the teaching and learning process. The intregation of media can stimulate students' attention and interest in learning. This research contains the development of E-Storyboard application media to teach English writing skills, especially recount text. Due to the importance of learning media the current research aims develop of E-Storyboard Application as media to teach English writing skill especially recount text. To achieve the goal of the reseach was implement ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The research subjects were 40 students of class X DPIB 2 and English teacher at SMK Islam 1 Blitar. There are two types of data in this research, namely qualitative and quantitative. The qualitative data was generated from observing the learning process and interviewing English teachers. While the quantitative data is generated from validation calculations and student response questionnaires. Product valization calculations use the percentage formula which results in an average of 89.5% in the "Very Valid" category. Then for the calculation of the student questionnaire using a Likert scale (1-4) and the index% formula to get a result of 80.3% which is in the "Very Angree" category. In summary the E-Storyboard application media product is accepted as an English language learning media, especially in writing recount text skills.